Simultaneous Detection of Herpes Simplex Virus Type 1 Latent and Lytic Transcripts in Brain Tissue. (February 2022) - Zhang, Shu; Zeng, Jianxiong; Zhou, Yuzheng; Gao, Ruoyun; Rice, Stephanie; Guo, Xinying; Liu, Yongzhen; Feng, Pinghui; Zhao, Zhen
Neurotrophic herpes simplex virus type 1 (HSV-1) establishes lifelong latent infection in humans. Accumulating studies indicate that HSV-1, a risk factor of neurodegenerative diseases, exacerbates the sporadic Alzheimer's disease (AD). The analysis of viral genetic materials via genomic sequencing and quantitative PCR (qPCR) is the current approach used for the detection of HSV-1; however, this approach is limited because of its difficulty in detecting both latent and lytic phases of the HSV-1 life cycle in infected hosts. RNAscope, a novel in situ RNA hybridization assay, enables visualized detection of multiple RNA targets on tissue sections. Here, we developed a fluorescent multiplex RNAscope assay in combination with immunofluorescence to detect neuronal HSV-1 transcripts in various types of mouse brain samples and human brain tissues. Specifically, the RNA probes were designed to separately recognize two transcripts in the same brain section: (1) the HSV-1 latency-associated transcript (LAT) and (2) the lytic-associated transcript, the tegument protein gene of the unique long region 37 (UL37). As a result, both LAT and UL37 signals were detectable in neurons in the hippocampus and trigeminal ganglia (TG). The quantifications of HSV-1 transcripts in the TG and CNS neurons are correlated with the viral loads during lytic and latent infection. Collectively, the development of combinational detection of neuronal HSV-1 transcripts in mouse brains can serve as a valuable tool to visualize HSV-1 infection phases in various types of samples from AD patients and facilitate our understanding of the infectious origin of neurodegeneration and dementia.